Azolla as an Economic Substitute to Soybean Based Feed for Poultry - Paudel, Dev Raj; Dhakal, Pramila; Timsina, Kailash P.; Dahal, Ananta (International Journal of Applied Sciences and Biotechnology, 2015)
A study on azolla as an economical substitute to soybean based poultry feed was conducted. The experiment consisted of four treatments laid out in Completely Randomized Design (CRD) with five replications. Each experimental unit consisted of three birds. For this purpose, eight-day old, unsexed Hubbard broiler chicks were weighed and randomly assigned to each treatment. Four different levels of azolla meal were incorporated in the starter and finisher ration at a level of 0%, 10%, 15%, and 20% respectively. Body weight, weight gain, feed consumption, and feed efficiency were measured. The average cumulative weekly body weight for all weeks were found to be significantly different (P